(3ahGFO CHj Ydi eMeO Hf CMeO Hf GdMSf GdUhGas - (3GdOQGbWfj , CHh GdMSf,J (B385 (3g` s
(3ChdgG (B:s
(3CNHQfG GdCNhGf Ce gGfi YajaI hCHh YHO Gddg eMeO GdaGQ aEfi HbQGAJi YdjgeG ai TgQ TYHGf SfI NeS hJSYjf hNeSeGFI s
(3BNQgG (B:s
(3bGd YeQ Hf GdNWGH QVi Gddg Yfg (B: (3HdZfi Cf GdC(B'(3eGd JHGgi aJbhd GdUObI CfG CaVdce BNQ GdLRA GdKGdK ef BLRGA GHf GdUhGa s
(3QhGjI GdMGaX CHj fYje CMeO Hf YHO Gddg Hf CMeO GdGUHgGfi s
(3YdjgG SeGYGJ HYVgG SfI (B517 (3hSeGY Ydi GdMGaX YHO GdZfi GdebOSi HefRdg HOeTb SfI (B624 (3Ke NW GdMGaX jhSa Hf GdRci GdeRis
(3JHUQI GdYfhGf (B:s
(3GNJjGQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B157s
Keywords: (3GdMOjK h GdeUWdMs